If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y + 7y = 0 Combine like terms: 6y + 7y = 13y 2x + 13y = 0 Solving 2x + 13y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. 2x + 13y + -13y = 0 + -13y Combine like terms: 13y + -13y = 0 2x + 0 = 0 + -13y 2x = 0 + -13y Remove the zero: 2x = -13y Divide each side by '2'. x = -6.5y Simplifying x = -6.5y
| 3c*d= | | 6(2a-3)-(7a+4)=2 | | 3v^2-2v^2+6=42 | | =4x^3-x^2-5x+7 | | ln(3x)= | | 9x+-4x=-20 | | 7x-8y=-21 | | 2p^3-5p^2-50p+125=0 | | 8a^3=72a | | 4(3x-1)=-7(-2x+3)+5 | | 4d+16=8d+2 | | 18h-1-9h=44 | | .5(8x-4)=3x-6 | | P-(-6)=5 | | 2n(2n)=24 | | n-3n=2x+6 | | 4z-10+10+5z=180 | | 3x-14=10x | | 0=4x-4 | | (X+18)+(3x-10)=180 | | -5v+29=-2v | | 98+z=114 | | 4z-10=10+5z | | n+27=83 | | X^5+5x+1=0 | | 67+x=114 | | f+23=54 | | 2.5+0.075n=0.1n | | 6y+11=9y-16 | | a+73=161 | | q-17=12 | | 7a-2b-6a-7b= |